Verbal Disagreements and Philosophical Scepticism. Issue 4 (1st October 2016) - Ballantyne, Nathan
ABSTRACT: Many philosophers have suggested that disagreement is good grounds for scepticism. One response says that disagreement-motivated scepticism can be mitigated to some extent by the thesis that philosophical disputes are often verbal, not genuine. I consider the implications of this anti-sceptical strategy, arguing that it trades one kind of scepticism for others. I conclude with suggestions for further investigation of the epistemic significance of the nature of philosophical disagreement.